Nutritional Status, Dietary Diversity and Household Food Security of Population in Arid Western Rajasthan - Srivastava, Soma; Singh, Bhagwan (Annals of Arid Zone, 2017)
The study uses cross-sectional data of a sample of 350 individuals from two villages of Jodhpur district of western Rajasthan. This paper examines the socio-demographic characteristics, extent of food security, diet composition and diversity as well as nutritional status at the household level. To this end, subjective and objective measures like Household Food Insecurity Access Scale (HFIAS) and Household Dietary Diversity Score (HDDS), 24-hr dietary recall and BMI were employed. Average HFIAS score of the villages were 0.83 and 0.90 representing 70-74% of population as food secure. Mild food insecurity was observed in the area specifically of qualitative nature rather than quantitative. Dietary diversity scores for the villages were 7.23 and 6.96. Per capita intake of calorie and protein were found 2001.04 kcal and 59.96 g, respectively. Dietary deficiency of fresh fruits and vegetables reflected in lower availability of beta-carotene and vitamin-C through the diet. Findings suggested that around 30% of the selected population was having low BMI and women were more prone to under nutrition compared to men.